2014
DOI: 10.37833/cord.v30i2.79
|View full text |Cite
|
Sign up to set email alerts
|

Status of Coconut Farming and the Associated Challenges in Kenya

Abstract: Coconuts (Cocos nucifera) have been grown in Coastal Kenya for many centuries and are an integral part of the farming systems in the region. Over 80% of the coastal farm households derive their livelihoods either directly or indirectly from the coconut tree that is considered as both cash and a food crop. The coconut tree on the other hand has a tremendous potential of helping Kenya’s poor in the coastal region and the rest of the country due to its multi-purpose uses that can be strategically harnessed to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This study used culture-independent approaches to investigate the diversity and composition of bacterial communities in coconut leaves showing symptoms of lethal yellowing disease and in healthy leaves, allowing for the identification of their abundance levels. While previous research in Kenya has reported the presence of bacterial pathogens in coconut palms (Pole et al, 2014), this study provides the first molecular evidence of their presence in coconut plants exhibiting yellowing symptoms. With 113,330 reads detected, NGS data revealed the diversity of the bacterial communities in the diseased and healthy coconut leaves, which included both cultivable and noncultivable bacteria.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This study used culture-independent approaches to investigate the diversity and composition of bacterial communities in coconut leaves showing symptoms of lethal yellowing disease and in healthy leaves, allowing for the identification of their abundance levels. While previous research in Kenya has reported the presence of bacterial pathogens in coconut palms (Pole et al, 2014), this study provides the first molecular evidence of their presence in coconut plants exhibiting yellowing symptoms. With 113,330 reads detected, NGS data revealed the diversity of the bacterial communities in the diseased and healthy coconut leaves, which included both cultivable and noncultivable bacteria.…”
Section: Discussionmentioning
confidence: 59%
“…A coconut baseline survey conducted by Kenya Coconut Development Authority (KCDA) shows that the tree population stands at 9,907,115 palms in the country, with Kwale and Kilifi counties having the highest population (Alpex Consulting Africa Ltd, 2013). Present nut production stands at 30 nuts per tree per year owing to poor management practices, a narrow genetic base, old and unproductive orchards, pests and diseases, with the latter being the major constraint in coconut cultivation (Manimekalai et al., 2014; Oyoo, 2021; Pole et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High rates of pests and diseases, poor agronomic practises, low-quality planting materials, and a limited genetic base are some of the difficulties [66]. In two papers published by Imminent, it is stated that climate change is causing West Bengal to experience a deficit in rainfall, more cyclones, and invasive pests.…”
Section: Resultsmentioning
confidence: 99%
“…Power outages, frequent pest and disease attacks, monsoon failure, high fertiliser and boosting chemical costs, a lack of high-quality fertiliser and boosting chemicals, groundwater depletion, and a lack of high-quality seedling availability are just a few of the factors that Premkumar [65] identified as contributing to cultivation and maintenance issues. As a result of high rates of pests and diseases, poor agronomic practices, substandard planting materials, and a small genetic foundation, low coconut yield is a problem [66]. According to Arifin [68] Lack of government assistance, a lack of human resources, and a lack of adequate infrastructure and facilities to support market activity for coconuts are the issues.…”
Section: Indiamentioning
confidence: 99%
“…In Kenya, Oryctes rhinoceros, locally referred to as "chongwa," is abundantly found in the coastal region (Mwachiro & Gakure, 2011). Though regarded as a highly destructive pest in coconut farms, causing damage to up to 80% of the palms (Wheatley, 2015;Pole et al, 2014), there are few undocumented cases in the coastal part of the country of heavy use of the Oryctes rhinoceros' larva as poultry feeds and some Mijikenda subcommunities of the Giriama, Chonyi, and Jibana consuming the beetle larva. Farmers cut down the infested palm trees to harvest the larvae from the tree trunks.…”
Section: Introductionmentioning
confidence: 99%